First record of Tuxophorus caligodes (Siphonostomatoida, Tuxophoridae) in sea-farmed cobia, Rachycentron canadum, in Brazil - Silva, Ana Carolina da [UNESP]; Moraes, Julieta Rodini Engrácia de [UNESP]; Antonucci, Antonio Mataresio; Shimada, Marina Tie [UNESP]; Takemoto, Ricardo Massato; Engracia Filho, Jair Rodini [UNESP]; Moraes, Flávio Ruas de [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2012)
O cobia é o único representante da família Rachycentridae e, devido às suas qualidades zootécnicas, a produção desse peixe tem sido implementada em vários países, tais como os Estados Unidos, México e Brasil. Tuxophorus caligodes é um parasito de peixes marinhos amplamente distribuído no mundo. Para o presente relato, 15 juvenis de cobias foram coletados de tanques-rede, em uma fazenda marinha em Ilhabela, Estado de São Paulo, Brasil, no inverno de 2011. Os peixes foram sujeitos à eutanásia por meio de concussão cerebral, pesados (280 ± 70,5 g) e medidos (27 ± 1,97 cm). Após exame externo sob um estereomicroscópio, os ectoparasitos presentes na superfície do corpo foram coletados, fixados e processados para identificação. Dos 15 peixes examinados, dois apresentavam-se parasitados indicando a prevalência de 13,3%. Esse é o primeiro relato de Tuxophorus caligodes em cobias no Brasil.

The cobia is the only representative of the Rachycentridae family and, because of its zootechnical qualities, production of this fish has been implemented in several countries, such as the United States, Mexico and Brazil. Tuxophorus caligodes is a widespread parasite of marine fish worldwide. For the present report, 15 juvenile cobias were collected from net cages on a fish farm in Ilhabela, state of São Paulo, Brazil, in the winter of 2011. The fish were sacrificed by means of cerebral concussion, and then weighed (280 ± 70.5 g) and measured (27 ± 1.97 cm). After external examination under a stereomicroscope, ectoparasites present on the body surface were collected, fixed and processed for identification. Out of the 15 fish examined, two were parasitized with Tuxophorus caligodes, thus indicating a prevalence of 13.3%. This is the first report of Tuxophorus caligodes in cobias in Brazil.
Primeiro relato de Tuxophorus caligodes (Siphonostomatoida, Tuxophoridae) em cultivo de cobias, Rachycentron canadum, no Brasil
Keywords: Ectoparasito; copépode; Rachycentron canadum; Brasil; Ectoparasite; copepod; Rachycentron canadum; Brazil